Understanding The Concept of Online Learning in Distance Learning amidst COVID-19 Crisis: Challenges and Opportunities - Renti R. Budiman (Sekolah Pascasarjana Universitas Brawijaya, 2021)
The outbreak of the COVID-19 caused educational institutions to cancel regular on-campus classes and forced them to initiate online learning with enhanced technology. This study aimed to explain how the concept of online learning was implemented as distance learning or Pembelajaran Jarak Jauh (PJJ) amid the COVID-19 crisis. This study used a qualitative method with a literature study. Findings revealed that the concept of online learning amidst pandemic as a crisis-response and emergency migration method is different from contemporary online learning. Emergency remote learning (ERL) has challenges and opportunities. The biggest challenge is logistic and internet connectivity. Moving forward, government, telecommunication companies, and educational institutions should cooperate and put an effort in developing internet infrastructure across the country as online learning will be the new norm in the foreseeable future.